Capsule Endoscopy Technology: A New Era in Digestive Tract Examination - Huang, Kang-ming; Qiu, Hua-bin; Deng, Yinghan; Wu, Lian-hui; Chen, Hong-bin (Journal of Digestive Endoscopy, 2024)
Capsule endoscopy (CE) represents an important groundbreaking advancement in gastrointestinal (GI) examinations, distinguished by its noninvasive, painless, and convenient nature, and has swiftly established itself as a crucial tool for diagnosing and treating digestive diseases. With the development of artificial intelligence (AI) and machine learning (ML), as AI and ML progress, the capabilities of CE have expanded beyond mere imaging within the GI tract; it is progressively evolving to encompass procedures such as biopsies and targeted drug delivery. This review systematically searched five reputable repositories—Scopus, PubMed, IEEE Xplore, ACM Digital Library, and ScienceDirect—for all original publications on CE from 2001 to 2024. The review provides an overview of the current status and identified limitations of CE, highlighting the significant role that AI and ML are projected to play in its future development.
Keywords: capsule endoscopy; endurance; image transmission; advancements in artificial intelligence; limitation